2020
DOI: 10.1097/md.0000000000019372
|View full text |Cite
|
Sign up to set email alerts
|

Apatinib combined with chemotherapy or concurrent chemo-brachytherapy in patients with recurrent or advanced cervical cancer

Abstract: Objective: Apatinib mesylate is a novel vascular endothelial growth factor receptor 2 (VEGFR-2) inhibitor, which has exhibited good safety and efficacy in several types of solid tumors. The present study aimed to assess the clinical efficacy and safety of apatinib combined with chemotherapy and concurrent chemo-brachytherapy (CCBT) in patients with recurrent and advanced cervical cancer. Methods: A total of 52 patients with first diagnosed recurrent or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…After screening and qualification evaluation, 23 clinical trials involving 6,241 patients were finally included after excluding review articles, case reports, and meta-analysis articles, with the flow chart of literature selection shown in Figure 1 . Of the 23 studies, there were 12 phase II, 11 phase III, and 1 phase IV trials, with the year of publication ranging from 2005 to 2020 ( Table 1 ) ( Miller et al, 2005 ; Heymach et al, 2008 ; Goss et al, 2010 ; Mok et al, 2011 ; Rugo et al, 2011 ; Baselga et al, 2012 ; Kato et al, 2012 ; Johnston et al, 2013 ; Laurie et al, 2014 ; Liu et al, 2014 ; Mackey et al, 2015 ; Rini et al, 2016 ; Baselga et al, 2017 ; Kubota et al, 2017 ; Yan et al, 2017 ; Dummer et al, 2018 ; Lu et al, 2018 ; Liu et al, 2019 ; Nakagawa et al, 2019 ; Cortot et al, 2020 ; Guo et al, 2020 ; Sinn et al, 2020 ; Tao et al, 2020 ). According to the published Common Terminology Criteria for Adverse Events (CTCAE) by the National Cancer Institute (NCI), hypertension caused by anti-cancer treatment includes 5 grades of grade 1–5 ( Table 2 ) ( National Cancer Institute, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…After screening and qualification evaluation, 23 clinical trials involving 6,241 patients were finally included after excluding review articles, case reports, and meta-analysis articles, with the flow chart of literature selection shown in Figure 1 . Of the 23 studies, there were 12 phase II, 11 phase III, and 1 phase IV trials, with the year of publication ranging from 2005 to 2020 ( Table 1 ) ( Miller et al, 2005 ; Heymach et al, 2008 ; Goss et al, 2010 ; Mok et al, 2011 ; Rugo et al, 2011 ; Baselga et al, 2012 ; Kato et al, 2012 ; Johnston et al, 2013 ; Laurie et al, 2014 ; Liu et al, 2014 ; Mackey et al, 2015 ; Rini et al, 2016 ; Baselga et al, 2017 ; Kubota et al, 2017 ; Yan et al, 2017 ; Dummer et al, 2018 ; Lu et al, 2018 ; Liu et al, 2019 ; Nakagawa et al, 2019 ; Cortot et al, 2020 ; Guo et al, 2020 ; Sinn et al, 2020 ; Tao et al, 2020 ). According to the published Common Terminology Criteria for Adverse Events (CTCAE) by the National Cancer Institute (NCI), hypertension caused by anti-cancer treatment includes 5 grades of grade 1–5 ( Table 2 ) ( National Cancer Institute, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…In 2019, several studies reported the effect of single‐agent apatinib treatment after failure of first‐line treatment in recurrent or advanced cervical cancer. 17 , 19 , 20 , 21 In 2020, Guo et al 22 assessed the clinical efficacy and safety of apatinib combined with chemotherapy or concurrent chemo‐brachytherapy as first‐line treatment. In comparison to the results from these studies, ORR, DCR and median PFS, and OS of our study seems a slightly higher than those reported in 2019, but lower than the finding from Guo et al in 2020.…”
Section: Discussionmentioning
confidence: 99%
“…Neratinib was generally well tolerated in the SUMMIT study and no new safety signals were identified. The efficacy of neratinib monotherapy was encouraging and, even though crosstrial comparisons are problematic, the ORR of 25%, CBR of 50%, and median PFS of 7.0 months observed in SUMMIT compare favorably with those reported for platinum-based chemotherapy plus bevacizumab [27,36] and other investigational agents tested in this setting including newer anti-VEGF and anti-PD-L1 therapies, such as apatinib [18,37], nivolumab [38], and pembrolizumab [28,29].…”
Section: Discussionmentioning
confidence: 87%